2007
DOI: 10.1094/mpmi-20-5-0547
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Nonstructural Protein ofTomato spotted wilt virusIs the Avirulence Determinant in the Interaction with Resistant Pepper Carrying theTswGene

Abstract: All known pepper cultivars resistant to Tomato spotted wilt virus (TSWV) possess a single dominant resistance gene, Tsw. Recently, naturally occurring resistance-breaking (RB) TSWV strains have been identified, causing major concerns. We used a collection of such strains to identify the specific genetic determinant that allows the virus to overcome the Tsw gene in Capsicum spp. A reverse genetic approach is still not feasible for TSWV; therefore, we analyzed reassortants between wild-type (WT) and RB strains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 51 publications
8
88
0
12
Order By: Relevance
“…Isolates from the GenBank containing most of these data were chosen to compare variations or mutations occurring in RB pepper strains. Similarly, to the results of Margaria et al [24], we detected several mutations both in NSs and N proteins, but there were not any of them common with all the RB strains. Controversially, with several plant viruses that interfere plant resistance by a 'gene for gene' interaction and the emergence of RB strains can be connected to specific point mutations (at given aa positions), TSWV RB strains evolve by different point mutations/substitutions at various aa positions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Isolates from the GenBank containing most of these data were chosen to compare variations or mutations occurring in RB pepper strains. Similarly, to the results of Margaria et al [24], we detected several mutations both in NSs and N proteins, but there were not any of them common with all the RB strains. Controversially, with several plant viruses that interfere plant resistance by a 'gene for gene' interaction and the emergence of RB strains can be connected to specific point mutations (at given aa positions), TSWV RB strains evolve by different point mutations/substitutions at various aa positions.…”
Section: Discussionsupporting
confidence: 90%
“…The rapid adaptation of TSWV to pepper resistance and breakdown of the Tsw resistance gene facilitated the determination of the avr factor (avr) of TSWV, and the study of the evolutionary aspects of emergence of new strains [15,[20][21][22][23][24][25][26][27]. However, contradictory results, lacking information and methodological difficulties hinder or delay advances in these questions.…”
Section: Discussionmentioning
confidence: 99%
“…the exchange of parts of genome segments during replication). Experimental selection of reassortants from plants coinfected by two TSWV isolates with contrasted biological properties allowed mapping the determinant for breakdown of the Tsw resistance to RNA S (Jahn et al, 2000;Margaria et al, 2007). Further studies have suggested contradictorily that the NSs nonstructural protein (Margaria et al, 2007) or alternatively the nucleocapsid protein (NP) (Lovato et al, 2008) coding regions of RNA S were involved in the breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…A classical test for revealing silencing suppressor activity was initially performed by co-agroinfiltrating 16C N. benthamiana with pBin-GFP (Margaria et al 2007) and each of the pBin61 derivatives of OuMV RdRp, MP, and CP previously described (Crivelli et al 2011). As positive control, we used the well-characterized silencing suppressor p19 of Tomato bushy stunt virus (TBSV), which exhibited suppression, but we failed to detect suppression activity with the OuMV MP, CP, or RdRp (not shown).…”
Section: Effects Of Mutations In the Kr Region On Host Rangementioning
confidence: 99%
“…For N. benthamiana agroinfection, each plasmid was transformed into Agrobacterium tumefaciens C58C1 and agroinfiltrated in young leaves, as previously described (Bendahmane et al 1999(Bendahmane et al , 2002Margaria et al 2007). To standardize the experiments, the absorbance (optical density at 600 nm) of the Agrobacterium cultures was measured and each agroclone was adjusted to a final concentration corresponding to an absorbance of 0.25.…”
Section: Agroinfection and Mechanical Inoculationmentioning
confidence: 99%